Relationship between the calculated oxygen activity and the sulfur partition ratio for CaO-Al2O3-SiO2-MgO slag during ladle refining - Slović, Zoran (Materiali in tehnologije, 2012)
A slag-metal equilibrium study was carried out to investigate the effect of oxygen activity on the sulfur partition for CaO-Alsub{2}Osub3-SiOsub2- MgO slag. The sulfide capacity Csubs prediction models by Sosinsky-Sommerville based on the optical basicity lambda and the KTH model in terms of the defined interaction coefficient of the component i to j xisupi-jsubInteraction is used in this work for both a comparison and an estimation of the sulfur partition ratio between ladle-treated slag and liquid steel. From the obtained results, it was shown that the Sosinsky-Sommerville optical basicity approach gives higher values for the sulfur partition ratio (Lsubs) compared with the KTH model.
Keywords: žveplo; žlindra; kisik; jeklo; porazdelitev; model KTH